Is burning mouth syndrome based on a physiological mechanism which resembles that of neuropathic pain? = Comparación entre el mecanismo fisiológico del síndrome de la boca ardiente y el dolor neuropático - Reyes Sevilla, Marisol
Burning mouth syndrome (BMS) is a chronic intraoral pain state that has been described as burning pain, tingling or numbness in the oral mucosa, in the absence of any organic disease. Most often affecting the tongue, anterior palate, and/or lips. The diagnosis of primary BMS is purely clinical and based on patients' description of typical subjective symptoms as well on the exclusion of any systemic or local factors that may give rise to secondary burning pain sensations within the oral mucosa. Relevant studies links BMS to a peripheral neuropathy and BMS patients have revealed distinct abnormalities within the trigeminofacial large and small fiber systems and the trigeminal brainstem complex. Therefore, treatment approach should involve a multidisciplinary character similar to the treatment for neuropathic pain including factors that might also play a role on the BMS etiology and pathophysiology.